ESG Practices in the Competitive Landscape of the US-China Electric Vehicle Industry: Tesla and BYD as an Example - Li, Yurui (Transactions on Economics, Business and Management Research, 2024)
This paper investigates the Environmental, Social, and Governance (ESG) practices of Tesla and BYD, prominent players in the global electric vehicle (EV) sector, and their influence on the competitive landscape. The analysis uncovers shared commitments to environmental sustainability and innovation yet also reveals distinctions in cultural factors, financial performance, and sustainability strategies. Challenges identified encompass supply chain management, regulatory compliance, and talent acquisition. Strategies proposed to overcome these obstacles include fostering strategic partnerships, diversifying procurement sources, and investing in employee development. The significance of this research lies in its contribution to understanding effective ESG integration within the EV sector, providing valuable insights for businesses seeking to enhance their sustainability practices. However, limitations such as reliance on secondary data exist, highlighting the need for future studies to incorporate primary data collection methods to enrich the analysis further. By expanding the understanding of ESG practices within the EV industry, this study offers actionable recommendations for companies to navigate challenges and capitalize on opportunities, ultimately fostering sustainable growth and innovation in the sector.